(untitled) (Modern education and development, 2025)
The article reviews algorithms for extracting informatics features from data using artificial intelligence methods. Extracting informatics features is the process of identifying important and useful information from a data set. This process is carried out, in particular, using natural language processing (NLP), machine learning (ML), and deep learning (DL) technologies. The article covers in detail the stages of data collection, preprocessing, feature extraction, and selection, as well as algorithms for extracting informatics features using machine learning and deep learning methods (e.g., SVM, KNN, CNN, RNN).